Dynamic simulation of a bioethanol distillation column in batch regime - Jara Morante, Eliana (2011)
Batch distillation is a process used in many industrial processes, from small to big scale, therefore it has a great commercial interest. In the process simulation context it presents challenges due to the system complexity, especially in the startup stage because there are many variables changing simultaneously. This work simulates the distillation process of a bench plant installed in the Unit Operations Laboratory of the FIQT of the UNI. Commercial simulation software ASPEN Batch Distillation V7.1 is used. The results are useful to establish a protocol of operation that allows us to obtain high bioethanol purity and the improvement of the process.